Unusual increase in carcinoembryonic antigen despite response to selpercatinib in two patients with medullary thyroid cancer - Stéphane Bardet; Renaud Ciappuccini; Livia Lamartina; Sophie Leboulleux (European Thyroid Journal, 2023)
Introduction: Serum calcitonin (CT) and carcinoembryonic antigen (CEA) are valuable tumour markers in patients with medullary thyroid carcinoma (MTC). Both markers most often evolve in parallel after treatment. Selpercatinib (LOXO-292) is a highly selective RET kinase inhibitor indicated in advanced RET-mutant MTC patients. Cases presentation: In this study, we report two observations of RET-mutant progressive metastatic and symptomatic MTC patients who were treated with selpercatinib. Patient 1, a 61-year-old man, presented dyspnoea and diarrhoea at selpercatinib initiation with large neck lymph nodes and lung metastases. Patient 2, a 76-year-old man, had acute discomfort with flush and diarrhoea, with small but diffuse bone and liver disease. Both patients had an objective tumour response with rapid clinical improvement and RECIST 1.1 response (−90%) in patient 1. A rapid dramatic decrease in CT level was observed in both patients (−99% in both patients), while CEA levels gradually and sustainably increased after selpercatinib initiation (+207% at cycle 15 in patient 1 and + 835% at cycle 14 in patient 2). In both patients, 18FDG PET/CT did not show any abnormal uptake that could explain the CEA increase. Colonoscopy and oesogastric fibr oscopy showed colonic polyposis with mild oesophagitis and gastritis in patient 1 and were normal in patient 2. Conclusion: These observations show an unusual and lasting increase in serum CEA in two MTC patients who exhibited an objective tumour response to selpercatinib. The mechanism behind this unexpected rise in CEA level remains unknown. The frequency of this evolving profile will be determined in further phase III studies.